2021
DOI: 10.1016/j.compscitech.2020.108560
|View full text |Cite
|
Sign up to set email alerts
|

An integrated computational materials engineering framework to analyze the failure behaviors of carbon fiber reinforced polymer composites for lightweight vehicle applications

Abstract: A bottom-up multi-scale modeling approach is used to develop an Integrated Computational Materials Engineering (ICME) framework for carbon fiber reinforced polymer (CFRP) composites, which has the potential to reduce development to deployment lead time for structural applications in lightweight vehicles. In this work, we develop and integrate computational models comprising of four size scales to fully describe and characterize three types of CFRP composites. In detail, the properties of the interphase region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 50 publications
(69 reference statements)
0
30
0
Order By: Relevance
“…It was found that the regions that undergo plastic deformation (grey color) are located in the thin cross sections in the FEM solid model, whereas they are much more extended towards the junctions in the FEM beam model (Figure 3). Sun et al [63] developed an Integrated Computational Materials Engineering (ICME) framework (Figure 4) to analyze the failure behavior of carbon fiber reinforced polymer (CFRP) composites used for lightweight vehicle applications. The properties of the interphase region have been determined by a molecular dynamics analysis and the analytical gradient model.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…It was found that the regions that undergo plastic deformation (grey color) are located in the thin cross sections in the FEM solid model, whereas they are much more extended towards the junctions in the FEM beam model (Figure 3). Sun et al [63] developed an Integrated Computational Materials Engineering (ICME) framework (Figure 4) to analyze the failure behavior of carbon fiber reinforced polymer (CFRP) composites used for lightweight vehicle applications. The properties of the interphase region have been determined by a molecular dynamics analysis and the analytical gradient model.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…According to the main problems of the macroscopic simulation study, a variety of strength failure theories are also put forward. However, the macroscopic simulation does not involve the micro mechanism of material failure, but predicts the failure behavior of the composite material structure through the material failure criteria [137][138][139]. Therefore, the macroscopic simulation is widely used in engineering practice and plays an important role.…”
Section: Macroscopic and Detailed View Simulationmentioning
confidence: 99%
“…Carbon-fiber-reinforced polymer (CFRP) composites with a high strength-to-weight ratio, stiffness-to-weight ratio, and corrosion resistance have gained substantial interest in numerous fields, such as aerospace, automobiles, sporting goods [ 1 ], etc. In the automotive industry, CFRP is one of the most promising alternatives to engineered metals for lightweight automotive structural components [ 2 , 3 , 4 , 5 ], and its demand has increased with the booming development of electric vehicles (EV) in recent years since lightweight designs comprise effective methods for optimizing the mileage of EV [ 6 , 7 ]. However, due to the low through-thickness thermal conductivity of CFRP [ 8 ], as well as the demand for homogeneous temperature distributions during the entire curing process for producing the desired part quality, the curing process of the CFRP normally features long processing times and high energy consumption, especially when this process is carried out in autoclaves.…”
Section: Introductionmentioning
confidence: 99%